Analytical Method Development And Validation Of Niclosamide By RP-HPLC. (International Journal of Food and Nutritional Sciences, 2022)
This research covers the development of an RP-HPLC method for estimating niclosamide. The developed method was verified in terms of Specificity, Accuracy, Linearity, LOD, LOQ, and Robustness according to ICH requirements. The precision findings for inter-day and intra-day were excellent enough to demonstrate that the proposed Method was exact and reproducible. The Assay experiment revealed that the niclosamide content measured in the tablet dose was free of excipient interference, indicating that the devised approach was specific. The recovery of standard drugs added was 99-100%.for niclosamide, indicating that the suggested approach was accurate. In the concentration ranges of 10-60 µg/ml, a good linear connection was seen for Standard Drug of niclosamide and Tablet Sample of nicosamide. Nicosamide correlation coefficient was determined to be 0.9999. Following analysis by many analysts, it was discovered that the RP-HPLC technique for the identification of niclosamide was robust. The % RSD for Robustness was well within the bounds, ensuring the suggested Method's robustness. The LOD for niclosamide Standard Drug was 0.2085 µg/ml. The LOQ of niclosamide for Standard Drug was determined to be 0.6321 µg/ml. This demonstrated that the developed RP-HPLC technique was simple, linear, precise, accurate, robust, and rugged, and that it could be easily used for routine quality control analysis of niclosamide from its pharmaceutical dosage form and bulk medication.